Blood Cell‐Derived Induced Pluripotent Stem Cells Free of Reprogramming Factors Generated by Sendai Viral Vectors. (11th July 2013) - Ye, Lin; Muench, Marcus O.; Fusaki, Noemi; Beyer, Ashley I.; Wang, Jiaming; Qi, Zhongxia; Yu, Jingwei; Kan, Yuet Wai
Abstract : This study demonstrated a reproducible protocol for reprogramming blood cells into transgene‐free induced pluripotent stem cells (iPSCs) using Sendai viral vectors. Creation of iPSCs, without integration of exogenous DNA, helps preserve genomic integrity and fosters the development of therapeutic‐grade stem cells for regenerative medicine. Abstract : The discovery of induced pluripotent stem cells (iPSCs) holds great promise for regenerative medicine since it is possible to produce patient‐specific pluripotent stem cells from affected individuals for potential autologous treatment. Using nonintegrating cytoplasmic Sendai viral vectors, we generated iPSCs efficiently from adult mobilized CD34 + and peripheral blood mononuclear cells. After 5–8 passages, the Sendai viral genome could not be detected by real‐time quantitative reverse transcription‐polymerase chain reaction. Using the spin embryoid body method, we showed that these blood cell‐derived iPSCs could efficiently be differentiated into hematopoietic stem and progenitor cells without the need of coculture with either mouse or human stromal cells. We obtained up to 40% CD34 + of which ∼25% were CD34 + /CD43 + hematopoietic precursors that could readily be differentiated into mature blood cells. Our study demonstrated a reproducible protocol for reprogramming blood cells into transgene‐free iPSCs by the Sendai viral vector method. Maintenance of the genomic integrity of iPSCs without integration of exogenous DNA should allow the development of therapeutic‐grade stem cells for regenerative medicine.